Investigating the effect of pore water composition and isosaccharinic acid (ISA) on sorption of Pu to a CEM III/C-based mortar - Coppens, Erik; Wouters, Katinka; de Blochouse, Benny; Durce, Delphine (Frontiers in Nuclear Engineering, 2023)
In the frame of the safe disposal of short-lived low and intermediate level nuclear waste (SL-ILW), ONDRAF/NIRAS (Belgium) has submitted a license application for the exploitation of a near surface facility in Dessel (Belgium). A significant part of the waste intended for the surface repository is Pu-contaminated and has been conditioned by means of CEM III/C based mortar, produced in the CILVA-installation at the Belgoprocess site in Dessel. To establish more accurate data on sorption of Pu to the CILVA mortar, an experimental test set-up was designed in order to screen which factors were likely to affect Pu sorption to the mortar. The different factors of the design were variables related to the pore water composition of the mortar on the one hand (concentrations of Ca2+, Cl-, SO42-, S2-, K+ and OH- (pH)), and variables characteristic for batch sorption experiments on the other hand ([Pu], solid-to-liquid ratio and equilibration time). The results of this screening indicate that over the tested variables, only the concentration of Ca2+ in the synthetic pore water affects Pu sorption to the CILVA matrix to a significant extent. Additionally, from literature it is expected that the presence of isosaccharinic acid (ISA), a cellulose degradation product, would affect Pu sorption (Wang, 2020), with increasing concentrations of ISA frequently correlated with decreased sorption. To address the nature and extent of the impact of both [Ca2+] and [ISA] and their combined effect on sorption of Pu to the mortar, an experimental set-up for surface response measurement (SRM) was designed. A Central Composite Design in two factors was selected for the SRM, with three test points and a four point repetition of the centre point. The execution of this experimental set-up and the resulting responses, allowed for the development of a polynomial model to predict the average response of Pu sorption (expressed as Rd) as a function of [ISA] and of [Ca2+]. In addition, the [Ca2+] in solution in equilibrium with the mortar could be assessed from the established dataset, which allowed to predict Pu sorption as a function of [ISA] at the intrinsic [Ca2+] in the mortar’s pore water.